THE USE OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS FOR INTEGRATIVE PURPOSES - D. F. Xamroqulova (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the importance of using innovative technologies and interactive methods in education, the formation of initial skills and competencies in students based on STEM educational programs, as well as the continuity in teaching young people how to use innovative technologies in their future activities.